Pelanggaran Hukum Dan HAM Pada Operasi Militer Di Aceh Sebelum Reformasi: Kajian Terhadap Kebijakan DOM - Indah Rahmawati Salim (CV. ITTC INDONESIA, 2024)
The Military Operations Area (DOM) policy implemented in Aceh before the reform era had serious implications for human rights violations (HRV) among civilians. This article examines various aspects related to HRV that occurred during this policy, as well as the accountability mechanisms for victims after the reform era. During the DOM period, numerous violations such as torture, extrajudicial killings, and enforced disappearances took place, while the government often failed to provide adequate accountability for the perpetrators. Although there is a legal framework supporting human rights protection, including Law No. 26 of 2000 on Human Rights Courts, its implementation faces various challenges, such as a lack of political support and weaknesses in law enforcement agencies. Furthermore, the role of civil society in promoting accountability and transparency is crucial. In legal settlement efforts, it is essential to involve various parties, including the government, society, and non-governmental organizations. The conclusion of this article highlights that to prevent future HRV, comprehensive reform in the legal system, human rights education, and enhanced cooperation between the government and civil society are necessary.